Woman Hymns and Christian Songs: Analysing women’s marginalisation in Kidung Jemaat - Tahan Mentria Cambah; May Linda Sari (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2022)
Singing is a tool used by Christians to worship. The song forms the attitude of its adherents by following the verses contained in the song. This paper aims to analyse the Kidung Jemaat song used by Christians in Indonesia using the lens of feminist theology. The dominance of the patriarchal concept causes an imbalance in relations between society and the church. The research was carried out by qualitative research, observing and carefully reading the poems used by the church in general, especially Kidung Jemaat. The study found that church hymns mention very little about women's stories, whereas the Bible talks about women's ministry in the community. The people's attitude was formed over the years, causing women to be marginalised in Christian singing. As a result, women are also marginalised in worship in the church and community. The church needs to encourage church musicians to create women's songs in the church.